2016
DOI: 10.1002/lno.10364
|View full text |Cite
|
Sign up to set email alerts
|

Consistency in coral skeletal amino acid composition offshore of Palau in the western Pacific warm pool indicates no impact of decadal variability in nitricline depth on primary productivity

Abstract: The depth of the thermocline and associated nitricline in the western Pacific warm pool (WPWP) vary over time in response to changes in larger ocean‐atmosphere climate patterns. A shoaling of the nitricline in the WPWP brings nitrate‐rich seawater ( NO3− > 4 μmol kg−1) above the base of the euphotic zone, stimulating primary productivity. Here, we test if decadal variability in the nitricline depth is driving changes in regional primary productivity and source nitrate dynamics. We use the nitrogen isotopic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Much of the recent work with proteinaceous deep-sea corals has focused on isotope analysis of total skeletal material as a proxy for changes in surface ocean conditions (e.g., Sherwood et al, 2005;Williams et al, 2007;Hill et al, 2014). However, CSIA-AA results can provide unprecedented reconstruction of past ocean conditions (Sherwood et al, 2011(Sherwood et al, , 2014Schiff et al, 2014;Strzepek et al, 2014;McMahon et al, 2015c;Williams et al, 2017). (Loder et al, 2001;Pershing et al, 2001), these authors concluded that changes in nitrate source partitioning may be tied to recent, human-caused changes in global climate.…”
Section: Case Study 3: Deep-sea Coralmentioning
confidence: 99%
“…Much of the recent work with proteinaceous deep-sea corals has focused on isotope analysis of total skeletal material as a proxy for changes in surface ocean conditions (e.g., Sherwood et al, 2005;Williams et al, 2007;Hill et al, 2014). However, CSIA-AA results can provide unprecedented reconstruction of past ocean conditions (Sherwood et al, 2011(Sherwood et al, , 2014Schiff et al, 2014;Strzepek et al, 2014;McMahon et al, 2015c;Williams et al, 2017). (Loder et al, 2001;Pershing et al, 2001), these authors concluded that changes in nitrate source partitioning may be tied to recent, human-caused changes in global climate.…”
Section: Case Study 3: Deep-sea Coralmentioning
confidence: 99%
“…It is therefore not implausible to assume that environmental conditions would have warranted a change in diet and possibly trophic level in the past. Compound-specific stable isotope analyses of amino acids (CSIA-AA) are increasingly becoming used as a paleoceanographic tool (Sherwood et al, 2011;Batista et al, 2014;Williams et al, 2017;McMahon et al, 2018), in part to address the issue of changes in trophic level influencing changes in  N values of the proxy archive. Nitrogen stored in amino acids is fractionated to different degrees dependent upon the metabolic pathway of the specific amino acid (McClelland and Montoya, 2002;Chikaraishi et al, 2007;Chikaraishi et al, 2009;McMahon and McCarthy, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Due to these diagnostic properties, CSIA-AA has been developed in the last several decades for a variety of applications broadly relating to food web dynamics and nitrogen cycling processes (see Ohkouchi et al, 2017 for a review), including using soft tissue of bivalves to reconstruct baseline  15 N conditions (Vokhshoori and McCarthy, 2014) and trophic position (Ek et al, 2018). This technique has also been used in a paleoceanographic context as a proxy for water mass source changes (Sherwood et al, 2011) and to reconstruct the depth of the nitricline through time (Williams et al, 2017). Despite the possible opportunities that  15 N and CSIA-AA  15 N in bivalve shells offers for paleoceanographic studies, there have only been a few reconstructions using these techniques that extend back beyond the instrumental record (Oczkowski et al, 2016;Darrow et al, 2017;Misarti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological variability makes a population more resilient, increases its ability to persist in variable environments and potentially forms the basis for selection (Gsell et al, 2012;Hattich et al, 2017). It is clear that other environmental factors such as light intensity, temperature, and nutrient concentration affect the responses of physiological rates of individual E. huxleyi strains to changing carbonate chemistry, and thus change the physiological variability within populations (Zhang et al, 2015;Feng et al, 2017). However, different sensitivities and requirements of each strain to the variable environments can allow strains to co-exist within a population in the natural environment (Hutchinson, 1961;Reed et al, 2010;Krueger-Hadfield et al, 2014).…”
Section: Physiological Responses Of Individual Strains To Pcomentioning
confidence: 99%